ANALISIS BUSINESS MODEL CANVAS MENGGUNAKAN PENDEKATAN SWOT PADA PERUSAHAAN PERKEBUNAN KELAPA SAWIT SG DI KABUPATEN SINTANG PROVINSI KALIMANTAN BARAT - Saptyawati, Laksmindra; Indah, Indah (Journal Competency of Business, 2022)
Indonesia is one of the largest CPO (Crude Palm Oil) producing countries in the world. In addition to producing CPO, oil palm fruit is also used as raw material for food and non-food production, alternative fuels, biodiesel development, and many others. SG's oil palm plantation, which is located in West Kalimantan, Sintang Regency, Kelam Permai District, is a company engaged in palm oil processing that was founded in 2008. In order to improve the quality of production, it is necessary to evaluate and analyze its business. So, the purpose of this study is to analyze the business model canvas using the SWOT method on the SG oil palm plantation company. The research method uses descriptive quantitative methods. The results showed that with a SWOT analysis approach, the SG oil palm company took advantage of the existing opportunities, namely the demand for fresh fruit bunches continued to increase in the market and government policies that supported the oil palm plantation business. SG's oil palm plantations must maintain the quality of fresh fruit bunches that will be sold to palm oil mills and increase the number of fresh fruit bunches harvested in order to remain competitive in the market. While the strategy for minimizing weaknesses is to improve good plantation maintenance techniques. As for the strategy, while maintaining good relations with partners, namely SG's oil palm plantations, the strategy for minimizing weaknesses and avoiding threats is to always cooperate with the Sintang Regency Government, West Kalimantan Province.